PROFESSIONAL STUDENTS IN PEDAGOGICAL HIGHER EDUCATION PEDAGOGICAL-PSYCHOLOGICAL CHARACTERISTICS OF THE DEVELOPMENT OF IDENTITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is devoted to the analysis of the pedagogical and psychological characteristics of the development of professional identity of future music teachers. The study studies the theoretical foundations of professional identity, factors influencing its formation, and the specifics of the process. The importance of national and international experiences, innovative pedagogical technologies, and digital tools in the development of professional identity of a music teacher is analyzed. The article presents recommendations on the introduction of special training and programs, the use of a person-centered approach, and interactive technologies to improve the quality of music education. This study represents scientific, theoretical, and practical approaches aimed at ensuring the professional growth and pedagogical effectiveness of music teachers. The article is intended for teachers, researchers, and educators working in the field of music education.